Dietary Derived Micronutrients Modulate Immune Responses Through Innate Lymphoid Cells - Shi, Zhengzheng; Ohno, Hiroshi; Satoh-Takayama, Naoko (Frontiers in Immunology, 2021)
Innate lymphoid cells (ILCs) are a group of innate immune cells that possess overlapping features with T cells, although they lack antigen-specific receptors. ILCs consist of five subsets-ILC1, ILC2, ILC3, lymphoid tissue inducer (LTi) cells, and natural killer (NK) cells. They have significant functions in mediating various immune responses, protecting mucosal barrier integrity and maintaining tissue homeostasis in the lung, skin, intestines, and liver. ILCs react immediately to signals from internal and external sources. Emerging evidence has revealed that dietary micronutrients, such as various vitamins and minerals can significantly modulate immune responses through ILCs and subsequently affect human health. It has been demonstrated that micronutrients control the development and proliferation of different types of ILCs. They are also potent immunoregulators in several autoimmune diseases and play vital roles in resolving local inflammation. Here, we summarize the interplay between several essential micronutrients and ILCs to maintain epithelial barrier functions in various mucosal tissues and discuss their limitations and potentials for promoting human health.